The influence of physical activity on the creativity of 10 and 11-year-old school children - Romance-García, Ángel Ramón; Nielsen-Rodríguez, Adriana; Mendes, Rui Sousa; Dobado-Castañeda, Juan Carlos; Dias, Gonçalo (Elsevier, 2023)
The benefits of physical activity in terms of physical and cognitive health are increasingly being studied and analyzed. However, divergent thinking has been scarcely studied in relation to the exercise performed. This study aimed to analyze whether there is a relationship between creative ability, intensity and amount of physical activity in 10–11 year old children. This research is framed within an ex post facto, descriptive, cross-sectional and correlational approach. The sample of this study consisted of 169 participants (82 boys and 87 girls), from a public Primary School center in southern Spain, aged between 10 and 11 years (M ± SD: age = 10. 48 ± 0.50 years). The amount and intensity of physical activity performed by students was measured by accelerometry, and the Torrance Test of Creative Thinking was used to evaluate the dimensions of creativity Originality, Fluency, Elaboration and Flexibility. All data collected was analyzed, using IBM-SPSS Statistics. Our results have revealed a correlation between the Cognitive Fluency, Originality and Cognitive Flexibility dimensions with moderate-vigorous physical activity. It is concluded that the "key to creativity" may depend on a combination of cognitive, social and family factors (among others). Although there is a tendency for a positive correlation between physical activity and creative ability, more studies are needed to better consolidate these assumptions.
Keywords: Creatividad (Educación); Deportes-Aspectos psicológicos; Physical activity; Creative ability; Torrance test of creative thinking; Embodied creativity; Cognitive health